60.8k views
1 vote
Given f(x) = -9x + 3 and g(x) = x4, choose

the expression for (fºg)(x).
Click on the correct answer.
-36x4 + 12
(-9x + 3)4
dxt + 3x4
-9x4+3

1 Answer

6 votes

Answer:

The correct answer is the last one, at the bottom.

Explanation:

You need to change in f(x) every 'x' for the expression given in g(x), since you have to build a compound function (fºg)(x).

So F(g(x))= F(x4)=-9*(x4)+3

Resulting (fºg)(x)=-9x4+3 (I only changed 'x' for 'x4', the term +3 is not changed since that is not a variable term, is just a constant number.

User Gravityboy
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.